Best Answer

5x-3 = 11+12x

5x-12x = 11+3

-7x = 14

x = -2

Q: How do you solve 5x-3 equals 11 plus 12x the solution is x equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

No solution. Multiply second equation by 3 and get 12x + 6y = 0 but already stated 12x + 6y = 9...

17

It is: 12x

6x + 12x + 2x = 80 20x = 80 x = 4

-12x = 72 Divde both sides by -12 to find the value of x: x = -6

Related questions

4x2 = -12x, divide both sides by 4x: x = -3

This is not an inequality. This is an equation.12x+7=43 12x=36 x=3

No solution. Multiply second equation by 3 and get 12x + 6y = 0 but already stated 12x + 6y = 9...

12x - 6 = 10x +2 12x - 10x = 2 + 6 2x = 8 x = 4

2*2 - 12x +16 =0 4 - 12x +16 =0 -12x + 16 +4 =0 -12x + 20 =0 -12x = -20 x = 1.666666667

Since that isn't an equation, there is really nothing to solve.

17

2x(3x+6) = 0 x = 0 or x = -2

There is no integer solution. Quadratic formula gives x = -17.66 or 5.66

12x + 17 = 7 Subtract 17 from both sides: 12x = -10 Divide both sides by 12: x = -10/12 = -5/6

the answer is-10 = 12 +xx= -10-12x=-22this is the answerx= -22

True because in both equations x = 0 or x = -4